Clinical Aspects and Therapeutic Perspectives of Relaxin - Bani, D.; Bigazzi, M. (Current Medicinal Chemistry - Immunology, Endocrine & Metabolic Agents, 2005)
Relaxin is a peptide hormone of the insulin/IGF superfamily best known for its effects on the female reproductive apparatus. In recent years, evidence has been accumulating that relaxin can have multiple and diverse effects on both reproductive and non-reproductive organs, tissues and cells, including blood vessels, heart, brain, kidney, liver, lung, immune and inflammatory cells. Despite this, identification of the possible roles of relaxin in the pathophysiology of diseases, not to mention the possible therapeutical applications of relaxin, remains an extremely difficult task. Based on its collagen remodeling properties, relaxin has been formerly used in obstetrics as a cervical ripener for labor induction, but with little or no benefit. Clinical trials with human recombinant relaxin in scleroderma patients gave only a slight improvement of the parameters under evaluation, but on the other hand, offered clear evidence that relaxin does not have substantial adverse effects, even at high doses. Based on the known biological effects of relaxin, it comes out that the potential fields of clinical investigation of human relaxin as a drug could be in plastic surgery (skin expansion), in orthodontics (tooth movement), in fibrosis and inflammatory diseases of different organs (liver, kidney, lung, heart), in ischemic heart disease (acute and chronic myocardial infarction), and in obliterative peripheral arteriopathy. Availability of the homologous human peptide, knowledge of its pharmacological, pharmacocynetical and pharmacodynamic profiles, and increasing interest and investments of pharmaceutical companies should be the main ingredients of the magic potion to change relaxin from a laboratory tool to a real drug.
Keywords: allergic asthma